Visual and emotional environmental interpretation of landscapes and nature scenes by American and Japanese elementary school children - Tsunoda, Tomoko (Kansas State University, 2007)
With the advancement of urbanization, many children today have limited or no experiences with nature or survival instincts as described by the nature (Biophilia) hypothesis. Today, children's preference toward landscapes may be more reflective of cultural experiences learned from family, teachers, or classmates, and referred to as the nurture hypothesis. In this research study, two visual surveys were used to investigate the nature vs. nurture hypotheses. In the first survey, 93 multicultural American children were asked to identify their preferred colors for symbols of bananas, tulips, birds, and trees. In the second survey, 202 children from American and Japanese schools were asked their visual preferences and emotional responses to photographs of landscapes, trees, homes, and nature scenes. Subjects were first, third, and sixth grade elementary school students in America and Japan. The effects of culture, age, and gender were evaluated. In addition, the relative preference and emotional impact of plants and landscapes were examined. In the first study, younger children preferred all colors that exist in nature. However, responses of the older children would support the nurture hypothesis. Older children selected fewer and more appropriate colors, such as yellow bananas, reflecting a learned behavior. Also, boys preferred blue symbols while girls selected red with higher frequency than other colors. In the second study, American children preferred the Japanese landscape and tree scenes, and reported more positive emotion than Japanese children toward the American and Japanese tree scenes. Younger American children showed more positive emotions toward the American home scene. Although first and third grade Japanese children preferred Japanese scenes, more sixth grade Japanese children preferred American scenes. In conclusion, visual preferences and emotional responses are influenced by content of photographs, and evidence supports both the nature and the nurture hypothesis among Japanese and American children.
Keywords: Visual preferences; Emotional responses; Landscape; Nature; Horticulture; Elementary school children; Agriculture, General (0473)